Effects of Altered Surface Inclinations on Knee Kinematics During Drop Landing - Cicily Hummer; Antonio Schefano; Kevin Valenzuela (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
Though it is well known that landing in an excessively inverted and plantar-flexed position commonly causes lateral ankle sprains, this landing motion has not been well studied for its effects on the knee joint. This study examines the effects of landing surface inclinations on knee kinematics during drop landing. Twelve recreational athletes performed five drop landings from an overhead bar with their feet 30 cm above three different surfaces: a flat surface, a 25° inversion surface, and a combined surface of 25° inversion and 25° plantarflexion. Threedimensional kinematic data was collected using a seven-camera Vicon system. Selected knee kinematic variables were assessed using a one-way repeated measure analysis of variance (p < 0.05). Landing on the combined surface resulted in a significantly reduced knee flexion range of motion (ROM, 44.7°) compared to landing on the flat surface (51.3°) and, thus, may likely incur greater knee joint loading due to increased stiffness in the joint. In addition, landing on the combined surface produced a 41% increase in knee abduction ROM compared to the inversion surface. Landing with decreased knee flexion and increased knee abduction ROM may predispose the anterior cruciate ligament to larger strains, thereby increasing the risk of anterior cruciate ligament injury.